BIAS GENDER TERHADAP PEKERJAAN DALAM BAHASA INGGRIS DAN BAHASA JERMAN DALAM GOOGLE TRANSLATE - Monica Melinda Putri Susanti; Wiwik Yulianti (Universitas Sebelas Maret, 2023)
The aim of this descriptive qualitative research is to compare the gender bias in the translation of Indonesian job names to English and German. This research was located in internet-based translation machine Google Translate. The examined data within are 22 Indonesian job names with its varied field. The samples are original job names in Indonesia, not the borrowed names from other languages and the ones with little potential of gender gap. This research is based on case study. With this method, researcher does translation of this data, but only ones in form of single nouns and nominal phrases. After that, English and German dictionaries were utilized to clarify, whether the results are classified as masculine, feminine or neutral. Human instrument is used with its capability and knowledge in gender classification of English and German job names. The outcome of this research reveal that in translation into English, the amount of masculine nouns emerge as the dominant or 13. The feminine nouns show up merely one. The number of the neutral one stands in between. The total is eight. This situation turns up as opposite in German. The neutral substantive can't be found. There are only 19 of masculine and three of feminine.Keywords: gender bias, google translate, job, translation